Synthesis and Characterization of Lignin-Based Polyurethane as a Potential Compatibilizer - Salma Ilmiati; Jana Hafiza; Jaka Fajar Fatriansyah; Elvi Kustiyah; Mochamad Chalid (Universitas Gadjah Mada, 2018)
Lignin is one of the most abundant biopolymer on earth. It has polar and non-polar side due to its hyperbranched structure, but the polarity of lignin has a higher tendency than non-polarity. Lignin has potential to be compatibilizer if the portion of non-polar can be increased. This research is focused on investigate the synthesis of lignin-based polyurethane to enhance the portion of non-polarity in lignin. Lignin-based polyurethane was prepared by reacting variation 4,4'-Methylenebis(cyclohexyl isocyanate) (HMDI) and polyethylene glycol (PEG), then lignin was added to the reaction. In this study, the structure of lignin-based polyurethane was confirmed by NMR and FTIR. NMR and FTIR showed that lignin successfully grafted. NMR, also used to investigate the variation molar mass of PEG and isocyanate contents effects to polarity of lignin-based polyurethane. The polarity of lignin-based polyurethane decrease as the composition of HMDI and molecular weight of PEG increase. This result also occurs on the sessile drop test that used to determine surface tension of lignin-based polyurethane. The thermal properties of lignin-based polyurethane also investigate using STA. Based on STA, enhancement of composition of HMDI and PEG increase thermal degradation and resistance of lignin-based polyurethane.